KCC2 Manipulation Alters Features of Migrating Interneurons in Ferret Neocortex. (6th April 2019) - Djankpa, F T; Lischka, F; Chatterjee, M; Juliano, S L
Abstract: KCC2 is a brain specific chloride–potassium cotransporter affecting neuronal development including migration and cellular maturation. It modulates chloride homeostasis influencing the switch of GABA from depolarizing to hyperpolarizing, which contributes to the cues that influence the termination of neuronal migration. The expression of KCC2 during migration of interneurons, therefore, correlates with the ability of these cells to respond to GABA as a stop signal. Manipulation of KCC2 in development can affect various aspects of migrating neurons, including the speed. We describe the effect of KCC2 downregulation and inhibition on features of migrating interneurons of normal ferret kits and those treated with methylazoxymethanol acetate, which increases KCC2. Treatment of organotypic cultures with Bisphenol A, an environmental toxin that alters gene expression, also downregulates KCC2 protein. In organotypic slices treated with the KCC2 antagonist VU0240551, chloride imaging shows inhibition of KCC2 via blockade of chloride flux. Time-lapse video imaging of organotypic cultures treated with either drug, shows a significant increase in the average speed, step size, and number of turns made by migrating neurons leaving the ganglionic eminence. Our findings demonstrate the harmful effect of environmental toxins on brain development and potential consequences in the pathogenesis of neurodevelopmental disorders.